MUNICIPAL ORGANIC WASTE AS SUBSTRATE OF BIOENERGY AND FERTILIZER PRODUCTION - Lies Sriwuryandari; T. Sembiring (Research Center for Chemistry - LIPI, 2010)
Municipal solid waste is still a big problem in the cities of Indonesia especially in the Capital and capital of province. Open dumping in TPA is operated through all of Indonesian cities, this bring to consequences a bad influence to the environment. Conversion of Organic solid waste either to energy or biofertilizer is one of the best choices on the solid waste management. These methods will create a good manageable of cities environment, producing fertilizer for the farmer, energy for the communal and jobs for the people. Municipal organic wastes were grinded andfermented in anaerobic aerobic conditions. Anaerobic conditions produce rrydrogen or methane as bioenergy meanwhile aerobic fermentation was used to get either compost or liquid oiofertilizer. The result of Bioenergy and biofertilizer production showed that Municipal organic waste has a great potential as substrate for bioenergy such as hydrogen and methane or substrate for biofertilizer. The biofertilizer could be either as compost or liquid biofertilizer which are rich with growth promoting substances produces by specific bacteria during municipal organic solid waste fermentation.Key words: Municipal, organic solid waste, management, bioenergy, bioJertilizer